Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy: Structural MR Imaging Changes and Apolipoprotein E Genotype - van den Boom, R.; Lesnick Oberstein, S.A.J.; van den Berg-Huysmans, A.A.; Ferrari, M.D.; van Buchem, M.A.; Haan, J. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Apolipoprotein E (apoE) genotype plays an important role in the development, maintenance, and response to injury of the central nervous system. It has been suggested that apoE ε4 genotype is a risk factor for several neurologic disorders. We investigated the correlation between the apoE genotype and radiologic data in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL).METHODS: T1-weighted, dual fast spin-echo, T2*-weighted gradient echo, and fluid-attenuated inversion recovery MR imaging scans were obtained from 36 CADASIL patients (21–59 years of age). The number of lacunar infarcts and microbleeds and the presence of subcortical lacunar lesions were determined. The amount of white matter hyperintensities was assessed by using semiautomated segmentation software. The relation between the radiologic endophenotype of CADASIL and the apoE genotype was assessed by using a Student t test for unpaired data and Fisher exact test.RESULTS: White matter hyperintensities, lacunar infarcts, microbleeds, and subcortical lacunar lesions were not found to be associated with the presence of an ε4 allele.CONCLUSION: The variability of structural MR imaging lesions in CADASIL is independent of apoE genotype and other processes must underlie the variable natural history of the disease.